2010
DOI: 10.1007/s10661-010-1375-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate levels modulate denitrification activity in tropical mangrove sediments (Goa, India)

Abstract: A study to examine the short-term effect of nitrate and organic carbon addition on denitrification activity was carried out on sediments from a mangrove ecosystem prone to anthropogenic activities (Divar, Goa, India). Laboratory microcosms were prepared using sediment sectioned at every 2-cm-depth interval from the surface to 10 cm. The incubations were subjected to varying nitrate amendments at concentrations ranging from 0, 5, 10, 20, 40 to 60 μmol l(-1) (up to three times more than measured in field). Nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…3), indicating that NO3 -was a limiting factor for N2O emission. Our result is in agreement with previous studies 13) 32)33) . King and Nedwell (1987) 33) showed that the bacterial communities responsible for N2O emission were adapted to changes in NO3 -concentrations.…”
Section: Nitrate Affected N2o Emission From Ru Cha Mangrove Sedimentsupporting
confidence: 94%
See 2 more Smart Citations
“…3), indicating that NO3 -was a limiting factor for N2O emission. Our result is in agreement with previous studies 13) 32)33) . King and Nedwell (1987) 33) showed that the bacterial communities responsible for N2O emission were adapted to changes in NO3 -concentrations.…”
Section: Nitrate Affected N2o Emission From Ru Cha Mangrove Sedimentsupporting
confidence: 94%
“…Nitrous oxide emissions depend on numerous factors such as NO3 -concentration, oxygen levels, pH, salinity, temperature, organic matter availability and microbial population 8)9)10)11) . Regarding geographical distribution, mangroves are found in South China 12) , Taiwan 4) , Puerto Rico 2) , India 3) 13) , Australia 14) . There are considerable uncertainties about sediment properties and environmental conditions in mangroves that would affect N2O emission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundant organic matter in coastal and estuarine systems generates favourable conditions for the heterotrophic denitrifiers to proliferate [14]. However, in such ecosystems, the persistent accumulation of aromatic hydrocarbons will inevitably render an effect on the physiological activities of the autochthonous microbial communities [12], such as, membrane transport [15], denitrification [16] and pigment production [17].…”
Section: Introductionmentioning
confidence: 99%
“…These areas include flooded rice fields (Reddy and Patrick 1986;Buresh and De Datta 1990), riparian wetlands (Hefting et al 2004;Van den Heuvel 2010) and mangrove forests (Chiu et al 2004;Fernandes and Loka 2011). In such flooded soils, the main products of denitrification (N 2 O or N 2 ) were dependent on environmental conditions.…”
Section: Introductionmentioning
confidence: 99%